Lignocellulose−based insulation materials: A review of sustainable and biodegradable solutions for energy efficiency - Mohsin Raza; Ayda Farhan; Basim Abu-Jdayil (International Journal of Thermofluids)
This review aims to comprehensively consolidate the knowledge and understanding of the development of thermal insulation materials for buildings using lignocellulosic waste materials. The building sector currently accounts for approximately 40 % of global energy consumption. Lignocellulosic waste materials are abundantly available worldwide, with their effective repurposing imperative to achieve positive environmental impacts. Lignocellulosic waste can be directly employed as a thermal insulator with minor modifications and binders. These materials consistently exhibit thermal conductivities below 0.1 W/m.K, the defining criterion for effective thermal insulation. An alternative strategy involves incorporating lignocellulosic waste as a filler or reinforcement agent within thermoplastics and thermosets to enhance their physicochemical attributes and render them suitable as thermal insulators. This approach aligns with sustainability principles and enables the replacement of 30–50 % of the polymer content with renewable material, with the resultant thermal conductivity values in these investigations also below 0.1 W/m.K. Moreover, with interest centered on the integration of lignocellulosic waste into the modification of biodegradable polymers to produce thermal insulation materials, prospects are promising for utilizing treated lignocellulose, cellulose, and their derivatives (such as nanocellulose and microcrystalline cellulose) as economical materials for developing biodegradable insulators. This review presents a thorough analysis and comparison of these approaches, providing researchers with insights for designing future research methodologies and addressing existing gaps in knowledge.